Pengelolaan Data Sektoral Melalui Program Magang Satu Data Sumatera Selatan Pada Dinas Pekerjaan Umum Bina Marga Dan Tata Ruang Provinsi Sumatera Selatan - Velisa Destiria; Gusmelia Testiana (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
The implementation of the One Data Indonesia policy has encouraged government institutions to strengthen sectoral data governance in order to support evidence-based public administration. As one of the Regional Government Organizations, the Public Works Highways and Spatial Planning Office of South Sumatra Province is responsible for managing and providing sectoral data through the South Sumatra One Data Portal. This study aims to examine the implementation of sectoral data management during the internship program at the institution. A descriptive qualitative method was employed using observation, documentation, and direct participation in daily work activities. The results reveal that the data management process consists of data collection, metadata preparation, verification, data entry into the CKAN-based South Sumatra One Data Portal, validation, and administrative documentation. Throughout the internship, several challenges were identified, including incomplete supporting documents, the need for repeated verification, and coordination among work units to ensure data quality and consistency. The internship provided practical insights into the importance of data governance, collaboration, and accuracy in managing government data. Overall, effective sectoral data management supports the availability of reliable information that can be utilized for planning, monitoring, evaluation, and policy formulation within the Provincial Government of South Sumatra.